Job Commitment among Agriculture Development Officers and Horticulture Development Officers of Punjab - Singh, Varinder; Kaur, Prabhjot (Indian Journal of Extension Education, 2015)
The present study is conducted to know the job commitment among agriculture district officers (ADO) & horticulture  district officers (HDO) of state department of agriculture and horticulture department of Punjab state. 120 ADOs and  HDOs was selected by using probability proportion to their numbers. It was found that majority of HDOs and ADOs have  medium level of commitment toward their job age and service experience of the respondents were found positively and  significantly associated with their job commitment.
Keywords: Job commitment; agriculture; horticulture